The curricular changes occurred in the training of teachers of primary education in Cuba from 1972 to 2010: implications - Jorge Alejandro Laguna Cruz (Universidad del Magdalena, 2014)
The article presents results of a study on the main changes in the curriculum of initial teacher training for primary education (from 1st to 6th grades) occurred in Cuba, and its impact on developing skills to use working with maps as a method to teach the school to locate, interpret and explain the objects and phenomena of geographical space. The elementary school curriculum requires greater use of cartographic materials. These demands require constant attention paid to the preparation of teachers in training map, however, research conducted by the author, show that the curricular changes that occurred in the training of teachers of primary education in Cuba in the last forty years have not paid enough attention to this problem.